Anisotropic Foams via Frontal Polymerization. Issue 8 (15th January 2022) - Alzate‐Sanchez, Diego M.; Cencer, Morgan M.; Rogalski, Michael; Kersh, Mariana E.; Sottos, Nancy; Moore, Jeffrey S.
Abstract: The properties of foams, an important class of cellular solids, are most sensitive to the volume fraction and openness of its elementary compartments; size, shape, orientation, and the interconnectedness of the cells are other important design attributes. Control of these morphological traits would allow the tailored fabrication of useful materials. While approaches like ice templating have produced foams with elongated cells, there is a need for rapid, versatile, and energy‐efficient methods that also control the local order and macroscopic alignment of cellular elements. Here, a fast and convenient method is described to obtain anisotropic structural foams using frontal polymerization. Foams are fabricated by curing mixtures of dicyclopentadiene and a blowing agent via frontal ring‐opening metathesis polymerization (FROMP). The materials are characterized using microcomputed tomography (micro‐CT) and an image analysis protocol to quantify the morphological characteristics. The cellular structure, porosity, and hardness of the foams change with blowing agent, concentration, and resin viscosity. Moreover, a full factorial combination of variables is used to correlate each parameter with the structure of the obtained foams. The results demonstrate the controlled production of foams with specific morphologies using the simple and efficient method of frontal polymerization. Abstract : A fast and convenient method to obtain anisotropic structural foams using frontal polymerization is described. A full factorial combination of variables is used to correlate the input parameters with the structure of the obtained foams. This work shows promise for creating foams with aligned cellular structures that allow anisotropic mass and energy transport properties in high‐performance structural solids.